1951
DOI: 10.3133/cir83
|View full text |Cite
|
Sign up to set email alerts
|

Geology and ground-water resources of the Helena Valley, Montana, with a section on the chemical quality of the water

Abstract: A study of the geology and the groundwater conditions of the Helena Valley, in the west-central part of Montana, was made during the summer of 19*^80 The purpose of the study was to gather data on the occurrence of ground water and its relation to present and proposed irrigation in the area. With such data one may better predict the effects of the application of irrigation water to additional lands in the area. 2 GEOLOGY AND GROUNDWATER RESOURCES OF THE HELENA VALLEY, MONTANA Ground vaters in the valley contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The central part of the Helena Valley-including most of the Irrigation District-is a ground-water discharge area. Although previous investigators (Wilke and Coffin, 1973;Lorenz and Swenson, 1951) considered surplus irrigation water to be the major source of recharge to the alluvial aquifer, Briar and Madison (1992) concluded that subsurface flow from fractures in the surrounding bedrock mountains accounts for nearly half (46 percent) of the recharge. Recharge also enters the alluvial aquifer by infiltration from irrigated fields (31 percent), seepage from canals (8 percent), and seepage from streams (15 percent).…”
Section: Hydrologic Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…The central part of the Helena Valley-including most of the Irrigation District-is a ground-water discharge area. Although previous investigators (Wilke and Coffin, 1973;Lorenz and Swenson, 1951) considered surplus irrigation water to be the major source of recharge to the alluvial aquifer, Briar and Madison (1992) concluded that subsurface flow from fractures in the surrounding bedrock mountains accounts for nearly half (46 percent) of the recharge. Recharge also enters the alluvial aquifer by infiltration from irrigated fields (31 percent), seepage from canals (8 percent), and seepage from streams (15 percent).…”
Section: Hydrologic Settingmentioning
confidence: 99%
“…Previous investigations of water resources in the Helena Valley have focused on the hydrogeology of shallow aquifers (Lorenz and Swenson, 1951;Wilke and Coffin, 1973;Wilke and Johnson, 1978;and Moreland and Leonard, 1980). Stickney( 1987) mapped surficial geological deposits of the valley.…”
Section: Previous Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed descriptions of the geology can be found in reports by Knopf (1913), Lorenz and Swenson (1951), Knopf (1963), andSchmidt (1977).…”
Section: Geohydrologic Settingmentioning
confidence: 99%